DETERMINANTS OF CORPORATE DIVIDEND POLICY -- A STUDY OF THE RETAIL SECTOR IN UK - Xie, Ying (2009)
It is indisputable that dividend policy is widely regarded as one of the most controversial subjects in the field of corporate finance. There are a number of different views on dividend policy. Some researchers argue that dividends are irrelevant; others, however, hold the opinion that dividends can increase or decrease shareholders’ wealth. The main value of this study is the identification of what factors affect corporate dividend policy and an attempt to empirically analyze the determinants of dividend payout of UK retail sector. Employing panel data methodology (pooled model, fixed effects model, random effects model and static panel data model), all UK publicly traded companies in the retail sector listed on the London Stock Exchange between 2000 and 2009 are examined. The study develops seven research hypotheses, which are used to represent the main theories of corporate dividends. As expected, based on 311 usable responses, the empirical results show that dividend payout ratio is positively related to profitability, but negatively to financial leverage, at a 5 % level of significance.